Efficient palladium (II) electrocatalysts with thiophene anchored pyridinium amidates for CO2 reduction. Issue 44 (February 2021) - Idrees, Muhammad Zaeem; Ilahi, Ibtasam; Ali, Muhammad Zeeshan; Muhammad, Zulqarnain
Highlights: Steric and electronic tunning of Pd (II) based homogeneous electrocatalyst for CO2 reduction with adaptive N-donor Pyridinyldine amides (PYA) anchoring thiophene as spectator ligands. Amongst the efficient catalyst with overpotential, TOF of −340 mV and 337s −1 respectively for CO2 reduction into CO. No change in characteristic peak of cyclic voltammetry after three hours of bulk electrolysis. Abstract: Palladium(II) complexes namely [Pd(LMe )2 (Cl)2 ] (5 ), [Pd(LEt )2 (Cl)2 ] (6 ), [Pd(LBu )(Cl)2 ] (7 ) and [Pd(LBz )(Cl)2 ] (8 ) were synthesized as electrocatalysts towards CO2 reduction into CO, H2 O acting as proton source in presence of TFA. These catalysts were prepared by substitution of benzonitrile from bis(benzonitrile)palladium(II)chloride with proligands; [HLMe ][OTf] (1 ), [HLEt ][I] (2 ), [HLBu ][Br] (3 ) and [HLBz ][Cl] (4 ) correspondingly. All the eight new compounds were successfully characterized with spectroscopic and single crystal X-ray diffraction techniques. It was found out that both steric and electronic properties of ligands concomitantly affected the catalytic properties of the catalysts. The activity of these catalysts decreases in the following order: 6 > 7 > 5 > 8 . 6 displayed maximum TOF of 337 s −1 and rate constant (kcat ) of 1870 M −1 s −1 along with 73 % Faradaic efficiency to produce CO from CO2 in the presence of trifluoracetic acid. However, the lowest over potential (η) of −340 mV was shown by 7 . All the catalysts were robust with no major current fluctuations were observed during controlled potential electrolysis for more than 3600 s.